2014
DOI: 10.1371/journal.pone.0102107
|View full text |Cite
|
Sign up to set email alerts
|

Robust Radiomics Feature Quantification Using Semiautomatic Volumetric Segmentation

Abstract: Due to advances in the acquisition and analysis of medical imaging, it is currently possible to quantify the tumor phenotype. The emerging field of Radiomics addresses this issue by converting medical images into minable data by extracting a large number of quantitative imaging features. One of the main challenges of Radiomics is tumor segmentation. Where manual delineation is time consuming and prone to inter-observer variability, it has been shown that semi-automated approaches are fast and reduce inter-obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
405
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 514 publications
(430 citation statements)
references
References 30 publications
(43 reference statements)
8
405
0
6
Order By: Relevance
“…ID and IDM measure the level of local homogeneity within the tumor volume. Their methods of calculation are based on assuming larger values for smaller gray‐tone differences in pair elements within the gray‐level co‐occurrence matrices (GLCM) 23, 66. Also, they are formulated to have a maximum value when all elements in the image are of equal values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ID and IDM measure the level of local homogeneity within the tumor volume. Their methods of calculation are based on assuming larger values for smaller gray‐tone differences in pair elements within the gray‐level co‐occurrence matrices (GLCM) 23, 66. Also, they are formulated to have a maximum value when all elements in the image are of equal values.…”
Section: Discussionmentioning
confidence: 99%
“…Also, they are formulated to have a maximum value when all elements in the image are of equal values. Therefore, these features are characterized by high sensitivity to the presence of adjacent diagonal elements in the GLCM 65, 66. These characteristics might lead to their remarkable insensitivity toward variation of the studied parameters.…”
Section: Discussionmentioning
confidence: 99%
“…While there are several functioning approaches [14,15], this aspect currently poses a challenge for radiomics.…”
Section: (Semi-) Automated Segmentation Of Image Filesmentioning
confidence: 99%
“…In addition to classic statistical analytical methods, approaches such as, for example, machinebased learning, are also pursued [14,17].…”
Section: Analysis Of Image-based Features In Association With Clinicamentioning
confidence: 99%
“…In the previous work, it has been proposed that radiomics has an ability of capturing tumor heterogeneity and connecting with genomics. In prior work, it has been found that the reproducibility of features depend on the robust of segmentation algorithms, which should provide an accurate and reproducible results [5]. Furthermore, semi-automated segmentation have a better similarity index (SI) than manual segmentation (the SI of machine-segmented lesions SI >0.93, whereas the SI of manual segmentation SI was 0.73) [6].…”
Section: Introductionmentioning
confidence: 99%